2019
DOI: 10.1097/md.0000000000015045
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors analysis of nosocomial pneumonia in elderly patients with acute cerebral infraction

Abstract: To investigate the risk factors of nosocomial pneumonia (NP) in elderly patients with acute cerebral infarction (ACI). In this study, 324 aged 70 years and over patients with ACI who were admitted to the inpatient department of TianJin First Hospital (China) from January 2012 to February 2018 were retrospectively analyzed. The patients were divided into NP group (80 patients) and non-NP group (244 patients) according to whether NP was occurred 48 hours after hospitalization. Baseline profiles and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…Furthermore, stroke severity, as measured by the NIHSS, was associated with SAP (OR=1.159). Many studies showed similar results, i.e., that patients with high NIHSS score were more likely to develop pneumonia after stroke,2527 which were consistent with our findings. Some studies showed that atrial fibrillation was significantly more prevalent in patients who developed pneumonia in the acute stroke stage, with ORs ranging from 1.96 to 3.30 2830.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, stroke severity, as measured by the NIHSS, was associated with SAP (OR=1.159). Many studies showed similar results, i.e., that patients with high NIHSS score were more likely to develop pneumonia after stroke,2527 which were consistent with our findings. Some studies showed that atrial fibrillation was significantly more prevalent in patients who developed pneumonia in the acute stroke stage, with ORs ranging from 1.96 to 3.30 2830.…”
Section: Discussionsupporting
confidence: 91%
“…The most common post-stroke infections are urinary tract infections, with rates as high as 1 in 4 patients [64], and pneumonia, with rates as high as 25 % [65]. However, not all of these infections are healthcare-associated-in one series, 24 % of stroke patients presented with an infection on admission [66].…”
Section: Ischemic Strokementioning
confidence: 99%
“…Well-documented predictors of post-stroke infection include older age, stroke severity, a larger area of the infarct, and dysphagia [68]. For pneumonia specifically, older age [69][70][71], male sex [70,72], current smoking [73], diabetes mellitus [72], hypertension [74], atrial fibrillation [65,75], congestive heart failure [71,75], chronic obstructive pulmonary disease [75], tachypnea and intubation [76], preexisting dependency [75,77], stroke severity [65,75,76], stroke subtype [76], dysphagia [76], and nutritional factors [65,75] have been found to pose risk. Stroke-associated pneumonia not only increases morbidity and mortality [78] but also clinical outcomes after discharge [65] as well as healthcare costs and LOS [79].…”
Section: Ischemic Strokementioning
confidence: 99%
“…Although studies of OI and pneumonia remain scarce, in different OI settings both DM and COPD have been identified as significant risk factors for nosocomial pulmonary infections, and patients with DM have been shown to have different and rarer bacterial strains and a significantly higher drug resistance rate than patients without DM [28][29][30][31]. In large cohorts, the pneumonia risk in DM patients seems obvious; López-de-Andrés et al [32] reported a 21% higher incidence of postoperative pneumonia in DM patients than in non-diabetic patients in a cohort of over 100,000 patients, although contradictory results have also been reported [33,34]. Associations between chronic pulmonary disease or DM and pneumonia were not verified in our study; however, the number of patients with a history of these diseases was too low for reliable statistical evaluation.…”
Section: Discussionmentioning
confidence: 99%